Uso da cannabis medicinal no tratamento da dermatite atópica canina - Mariga, Carollina (2023)
Dermatological consultations represent 40% of the routine in the small animal medical clinic, with canine atopic dermatitis (CAD) reported between 3 to 15% of the canine population. The role of the endocannabinoid system in the skin does not only reveal its direct action on homeostasis and its deregulation contributing to dermatopathies, but the detail of its presence in specialized skin cells reveals a delicate and complex therapeutic potential. Due to the difficulties and the growing scientific evidence of the therapeutic benefits of cannabis, this work aimed to evaluate the anti-inflammatory effect of cannabis oil in the treatment of this disease. For this, canines diagnosed with CAD were divided into two groups: the treated group [using full spectrum high cannabidiol (CBD) cannabis oil] and the control group (treated with olive oil). The evaluation methods for the effectiveness of the therapy were based on the degree of pruritus, dermatological evaluation through CADESI-4, measurement of interleukins 6, 10 and 31, oxidative stress and histopathological evaluation of the skin with mast cell count. Despite the theoretical basis, in this work no significant results were obtained between the compared treatments. Thus, it is concluded that the full spectrum high CBD cannabis oil presents a promising approach in the multi-target treatment of CAD, requiring further research to study its therapeutic value in this canine disease.